Effects of suspension density on microbial metabolic processes - Janda, S; Kotyk, A (Folia microbiologica, 1985)
Respiration of yeasts Saccharomyces cerevisiae, Rhodotorula glutinis, Endomyces magnusii, and Candida utilis, and of bacteria Escherichia coli and Bacillus megaterium, anaerobic production of CO2 by S. cerevisiae, active transport of quinovose by R. glutinis and of L-proline and L-leucine by S. cerevisiae were highly dependent on cell suspension density. Respiration of S. cerevisiae in the presence of glucose decreased in a biphasic fashion from 140 to 40 nmol O2 per mg dry solid per min as suspension density increased from 0.01 to 2 mg/mL. Higher partial pressures of oxygen further enhanced the trend. The active transports were affected monophasically in the maximum rate of uptake which was as much as ten times greater at low than at high suspension densities. A component of the external medium is suspected to cause the decrease of metabolic functions at higher cell densities, acting as a noncompetitive inhibitor. The component was present and mutually active in suspensions of the various yeasts as well as of bacteria. Its properties and results of model experiments suggest it to be dissolved carbon dioxide.
Keywords: houby; kinetika; Saccharomyces cerevisiae; anaerobióza; Biological Transport, Active; spotřeba kyslíku; Cell Membrane; Oxygen Consumption; Carbon Dioxide; Bacteriological Techniques; bakteriologické techniky; Fungi; Anaerobiosis; oxid uhličitý; Rhodotorula; Escherichia coli; Kinetics; buněčná membrána; aktivní transport; Saccharomycetales; Bacillus megaterium; Candida